(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2011)
The article deals with peculiarities of phonation phraseological units as the characteristics of manner of speaking. The author pays attention to such notions as “phonation”, “voice intensity”, “intonation”, determines the correlation between the units of verbal and non-verbal communication levels and underlines an emotionality of such expressions and their communicative values.